2021
DOI: 10.3389/fendo.2021.662725
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Polycystic Ovary Syndrome and Associations With the Vaginal Microbiome: A Cross-Sectional Based Exploratory Study

Abstract: BackgroundPrevious studies suggest that the vaginal microbiome is associated with polycystic ovary syndrome (PCOS). However, the clinical manifestations of PCOS are heterogeneous. Whether the vaginal microbiome is related with different clinical symptoms was unknown.Materials and MethodsIn this cross-sectional study, 89 female patients with PCOS admitted to Zhongda Hospital (Nanjing, China) were included. Basic demographic information, health-related behaviors, clinical manifestations and sex hormone levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Additionally, LPS and Vaginolysin which is a virulence factor secreted by membrane vesicles of Gardnerella vaginalis 53 can bind to the nod‐like receptor, generating the NLRP3 inflammasome complex, which can trigger the release of IL‐1β and IL‐18, causing inflammation 52 . Moreover, a study found a link between high AMH levels and vaginal Mycoplasma colonisation in women with PCOS and AMH which is a glycoprotein hormone that plays a vital role in growth differentiation and folliculogenesis and elevated amount of which can lead to anovulation, therefore this could be a possible link underlying microbiota influenced PCOS‐related clinical presentation 54,55 …”
Section: Oligo/anovulation and Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, LPS and Vaginolysin which is a virulence factor secreted by membrane vesicles of Gardnerella vaginalis 53 can bind to the nod‐like receptor, generating the NLRP3 inflammasome complex, which can trigger the release of IL‐1β and IL‐18, causing inflammation 52 . Moreover, a study found a link between high AMH levels and vaginal Mycoplasma colonisation in women with PCOS and AMH which is a glycoprotein hormone that plays a vital role in growth differentiation and folliculogenesis and elevated amount of which can lead to anovulation, therefore this could be a possible link underlying microbiota influenced PCOS‐related clinical presentation 54,55 …”
Section: Oligo/anovulation and Microbiomementioning
confidence: 99%
“…52 Moreover, a study found a link between high AMH levels and vaginal Mycoplasma colonisation in women with PCOS and AMH which is a glycoprotein hormone that plays a vital role in growth differentiation and folliculogenesis and elevated amount of which can lead to anovulation, therefore this could be a possible link underlying microbiota influenced PCOS-related clinical presentation. 54,55 Since ovulation is identified as a cytokine-regulated inflammatory pathway, and several member of the Toll-like receptor (TLR) are pre-sented on granulose cells and cumulus cells of ovulating follicles, inflammation which can induce expression of certain genes and may influence ovarian surface epithelial cells at the time of ovulation and any abnormality in the levels of these inflammatory factors can lead to infertility due to the altered gene expression patterns in ovarian cells [53][54][55] which is evidence suggesting microbiota can be correlated to clinical manifestations of PCOS, such as menstrual irregularities. While there is a little direct indication for the pathogenic bacteria related dysfunction in the ovary in case of PCOS, the microbiota's implication on the female genital system influencing PCOS is worth exploring and thus, additional research into microbiome and molecular pathways underlying with PCOS are required for a potential conclusion of the underpinning mechanism behind the correlation of microbiota and ovarian axis.…”
Section: Oligo/anovulation and Microbiomementioning
confidence: 99%
“…The swabs were transferred to a − 80 °C refrigerator, and saved for bacterial nucleic acid extraction. Following the standard procedures in our laboratory, [ 14 ] swabs were eluted in 2 ml PBS, and TIANamp Bacteria DNA Kits (Tiangen Biochemical Technology, Beijing, China) were used to extract and purify DNA. The concentrations of DNA were measured through Nanodrop one (Thermo Scientific Co.,Ltd., MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (qPCR) was used to measure the absolute loads of specific vaginal bacteria, including L. crispatus, L. gasseri, L. iners, Gardnerella vaginalis (G. vaginalis), and Fannyhessea vaginae (F. vaginae, also called Atopobium vaginae). We used specific primers that had been verified by previous studies (further details are given in Additional file 2: Table S1 [18][19][20][21]). We used the NCBI Blast database to predict the amplified products, and specific plasmids were synthesized by Sangon Biotech Company (Shanghai, China).…”
Section: Assessment Of Absolute Bacterial Loads and The Clustering Of...mentioning
confidence: 99%